Association between short-term exposure to air pollution and peptic ulcer bleeding: A case-crossover study in China. (1st July 2021) - Wu, Mengyin; Tang, Mengling; Yu, Zhebin; Mao, Xinli; Chen, Yi; Wang, Jianbing; Jin, Mingjuan; Yu, Chaohui; Chen, Kun
Abstract: Background: Air pollution has already become a serious public health concern worldwide, while evidence for the association between air pollution and digestive disease is not consistent. Objective: To examine the association between air pollution and peptic ulcer bleeding (PUB). Methods: We performed a time-stratified case-crossover study among 1, 246, 270 gastroscopy records in Zhejiang, China from January 1st, 2013 to June 30th, 2019. Individual exposure to air pollution for each subject was estimated by using data from 55 fixed-sites with an inverse distance weighted method. Conditional logistic regression models were used to estimate the odds ratios (ORs) and 95% confidence intervals (95% CIs) for PUB associated with an interquartile range (IQR) increase in air pollution on the entire population. Subgroup analyses were performed for season, age and sex. Results: Totally 3543 patients diagnosed with PUB were included in the analyses. Significant associations were observed between NO2, CO and PM2.5 and the risk of PUB. The effect was observed strongest measured as lag06 and an IQR increase of 7-day moving average concentrations of NO2 resulted in a 24.0% increase of getting PUB (95% CI: 2.6%–50.0%). Significance: Our findings strengthen the hypothesis that short-term air pollution exposure has adverse health effects on digestive system. Highlights: Air pollution has adverse health effects on respiratory and cardiovascular systems. The effects of air pollutants on peptic ulcer bleeding are still unclear. Short-term exposure to some air pollutants contribute to peptic ulcer bleeding.